Pulmonary artery injury in left atrial appendage closure device implantation: a systematic review of a potentially fatal complication. (25th November 2020) - Hanna, B; Desai, R; Sachdeva, S; Singh, S; Gangani, K; Taha, Y; Echols, M; Paul, T.K; Berman, A; Bloom, H; Kumar, G; Sachdeva, R
Abstract: Background: Pulmonary artery (PA) injury is a rarely reported complication following percutaneous left atrial appendage closure (LAAC). This study aims to systematically review all reported cases of PA injury associated with LAAC. Methods: PubMed/Medline, SCOPUS, EMBASE, Google Scholar and the MAUDE databases were searched to find studies reporting PA injury during or after LAAC with the Amplatzer Amulet (AA), Amplatzer Cardiac Plug (ACP) or Watchman device through October 2019. Categorical data were reported in terms of numbers and/or percentages (%). Results: We found 13 cases (mean age 71.4 yrs) with reported PA injury associated with LAAC. Of these, 9 were case reports, 3 were reported in observational studies, and 1 was in the MAUDE database. Most cases (n=8) were reported in Europe followed by Australia (n=2) and Asia (n=2). The indication for device implantation in all patients was a high bleeding risk with anticoagulation for atrial fibrillation. Five cases were reported with the ACP (1/5 patients died), 5 with AA (2/5 patients died), and 3 with the Watchman (1/2 patients died). Acute and late presentations following implantation were reported for all three devices. 69.2% of cases (9/13) occurred acutely (during or within 24 hours of intervention). Of these, 3/9 occurred during device implantation. 2/4 of the delayed cases occurred >2 weeks following implantation. The mortality rate for acute and delayed cases was 22% (2/9 patients) and 50% (2/4 patients), respectively. A majority of the cases were attributable to barb/strut/hook injury of the PA. PA injury was associated with a mortality rate of approximately 31%. All surviving patients were managed with surgical intervention. Conclusion: PA injury is an infrequently reported complication following LAAC and is associated with high mortality. Cases can present acutely (intra-procedurally or within 24 hours) or delayed (>24 hours post-implantation). A majority of cases are due to direct injury of the PA by the struts/hooks/barbs of the device. Practitioners should be cognizant of this life-threatening complication, which requires a high index of suspicion for diagnosis and can occur weeks after device implantation. Funding Acknowledgement: Type of funding source: None